Romania Toward a Low Carbon and Climate Resilient Economy : Water Sector Analysis - World Bank (World Bank, Washington, DC, 2016)
Romania’s water resources are moderate, but sufficient with prudent resource management that will ensure conservation and sustainability; regional and inter-annual variation is, however, significant. Water availability in Romania is only 2,000 cubic meters per capita per year, just above the international threshold for water stress of 1,700